"It's Valid and Reliable" Is Not Enough: Critical Appraisal of Reporting of Measures in Trials Evaluating Patient Decision Aids. (July 2014) - Sepucha, Karen R.; Matlock, Daniel D.; Wills, Celia E.; Ropka, Mary; Joseph-Williams, Natalie; Stacey, Dawn; Ng, ChirkJenn; Levin, Carrie; Lally, Joanne; Borkhoff, Cornelia M.; Thomson, Richard
Background. This review systematically appraises the quality of reporting of measures used in trials to evaluate the effectiveness of patient decision aids (PtDAs) and presents recommendations for minimum reporting standards.Methods. We reviewed measures of decision quality and decision process in 86 randomized controlled trials (RCTs) from the 2011 Cochrane Collaboration systematic review of PtDAs. Data on development of the measures, reliability, validity, responsiveness, precision, interpretability, feasibility, and acceptability were independently abstracted by 2 reviewers.Results. Information from 178 instances of use of measures was abstracted. Very few studies reported data on the performance of measures, with reliability (21%) and validity (16%) being the most common. Studies using new measures were less likely to include information about their psychometric performance. The review was limited to reporting of measures in studies included in the Cochrane review and did not consult prior publications.Conclusions. Very little is reported about the development or performance of measures used to evaluate the effectiveness of PtDAs in published trials. Minimum reporting standards are proposed to enable authors to prepare study reports, editors and reviewers to evaluate submitted papers, and readers to appraise published studies.